How digital social life matters : new frames for social and cultural analysis - Toews, David (Media, culture and critique: future imperfect, 2025)
"Focusing on two concepts that were central to modernism and continue to be important, albeit in different ways, this book explores the nature of the simple and the complex, and the relationship that exists between them. With attention to trends in big data and digital media, society, politics, and culture, and the shift from groups towards networks in social life, it considers how the simple is transformed by the new realities of the internet-powered, global society, and what its role might be in helping us to understand them, both from the point of view of methods in the social sciences and humanities, and in life. Rejecting the positivist idea that the simple remains a static background against which the open-ended complexity of our world continues to expand, the author contends that the growth in complexity is mirrored in the 'relativization of simplicity', a phenomenon that is highlighted by gradual social changes that the era of digital media is now making apparent. Through a series of questions raised by our new digital lives, How Digital Social Life Matters argues for significant changes in how we see the world. Focussing on the relationship between theory and methods, it offers a critical phenomenology of experiences associated with the network society and networked individualism in an era of 'big data'. It uses an examination of the concept and phenomenon of the simple, unpacking its new dynamics, its new meanings and its new depth, as a way of demonstrating the need for new conceptions of the complex in such contexts as reality, the universe, and the cosmos. As such, it will appeal to social theorists, communication scholars, and philosophers with interests in the fields of relational sociology, digital media, and object-oriented ontology. It also engages more broadly with scholars with a sociologically-informed interest in reimagining the social roles of politics, science, nature, media, globalization, the environment, and social interaction for our new digital era"--